High expression of cyclooxygenase-2 in high grade human prostate adenocarcinoma - Mohd Rohaizad Md Roduan; Norhafizah Mohtarrudin; Chong, Pei Pei; Malina Osman; Noraini Mohd Dusa (Universiti Kebangsaan Malaysia, 2015)
Inflammation plays an important role to the process of prostate carcinogenesis by increasing the rate of cell proliferation, which contributes to an aggressive tumour phenotype. Cyclooxygenase-2 (COX-2) has been found overexpressed in various types of cancer cells including prostate. The aim of this study was to investigate the COX-2 expressions in different types of human prostate tissues. Paraffin-embedded prostate tissues from 263 samples were examined for the expression of COX-2 marker by immunohistochemistry method. COX-2 was found highly expressed in prostate adenocarcinoma (p=0.001) as compared to benign and normal tissues. The score of COX-2 expressions in most of normal prostate was weak 49 (77.8%), while only 16 (16%) of BPH showed strong expression. 56 cases (56%) prostate cancer showed strong COX-2 expression. Prostate cancer cases showed significant differences in staining patterns as tumour grade increased. In addition, COX-2 expression was significantly correlated with Gleason score in cancerous tissues. This study suggests that COX-2 overexpression is associated with prostate cancer and higher grade tumour.